PRESERVATIVE EFFECT OF DIETARY OREGANO AND GERMANDER ON QUALITY AND STORAGE STABILITY OF RAW BROILER MEAT - M. S. AL-Rawashdeh; M. A. AL-Hijazeen; G. J. AL-Rabadi (Journal of Animal and Plant Sciences, 2022)
The effects of dietary Origanum syriacum L. and Teucrium polium L., alone and in combination, on the quality and stability of raw broiler meat were evaluated. Broilers (N=140 ) were reared for 21 days, divided into five groups under completely randomized design receiving one of five dietary treatments (w/w): 1) Control, 2) 1.5% germander (GER), 3) 2.5% oregano (ORE), 4) 1.5% ORE combined with 2.5% GER (CM), 5) 0.02% butylated hydroxyanisole (BHA). Meat was stored under refrigeration at 4 °C for up to 7 days, and analyzed for thiobarbituric acid-reactive substances (TBARS), protein oxidation, and CIE color values at 0, 4, and 7 days. A similar procedure was used for sensory evaluation and other quality measurements. Both CM and ORE treatments had the significant effect (P ≤ 0.05) on decreasing TBARS values. In addition, CM treatment had the greatest anti-carbonyl effect and exhibited the greatest stabilizing effect on L* values at day 7. CM and ORE treatments were also best able to maintain a* values. The preservative effect of ORE and CM was significantly higher (P ≤ 0.05), retarding the development of off-odor and rancidity. In conclusion, the current CM level still needs further investigation to be recommended as a commercial additive.
Keywords: Oregano; Germander; Dietary antioxidant; Lipid oxidation; Sensory attributes